Teacher E-professionalism: An Examination of Western Canadian Pre-service Teachers’ Perceptions, Attitudes, and Facebook Behaviours - Poth, Cheryl; McCallum, Kendra; Tang, Wei (Alberta Journal of Educational Research, 2016)
This study addresses the pressing need for attending to teacher e-professionalism, that is, the appropriate application of information and communication strategies when using digital media. The authors examine data patterns related to 113 pre-service teachers’ perceptions of e-professionalism, attitudes towards existing technology-related professional guidelines, and current behaviours on Facebook. The results from the online questionnaire suggest that these Western Canadian pre-service teachers are uncertain about what online behaviours should be restricted and whether maintaining e-professionalism was possible. Integrated findings are discussed in light of communication privacy management theory. The paper concludes by advancing implications for informing e-professional education for teachers. Cette étude adresse le besoin pressant pour assister e-professionnalisme d'enseignant, qui est, l'application appropriée de stratégies d'information et de communication lors de l'utilisation des médias numériques. Les auteurs examinent les configurations de données de 113 enseignants en formation liées à leurs perceptions d’e-professionnalisme, attitudes à l'égard des directrices professionnelles environ la technologie, et comportements actuels sur Facebook. Les résultats du questionnaire suggèrent que ces enseignants en formation de ouest canadiens sont incertains quant à ce que les comportements basés sur le Web devraient être limités et si maintenir e-professionnalisme était même possible. Les conclusions sont discutées utilisant une théorie de la gestion de la confidentialité des communications. L’article conclut en avançant des implications pour informer l'éducation d' e-professionnel pour les enseignants.